(untitled) (Journal of the College of Basic Education, 2022)
This research aims at knowing the effect of the style table Robin in for fifth grade female studentsbranch, The researchers adopted. On the experimental design with partial control, which is the design of the two experimental and control groups with a post-test, and in a random way they chose section (A) to represent the experimental group with (36) students and section (B) to represent the control group with (34) students, so the research sample amounted to (70) Students, and the researchers statistically rewarded between the two research groups in the following variables “chronological age, grades of the previous year, and the academic achievement of parents.” They prepared an achievement test consisting of (35) items. The first course) for the academic year (2021-2022), and they used the following statistical methods (test the thai for two eyes independent, and square kay, and coefficient Engagement Pearson, and coefficient difficulty, and strength Discrimination, and coefficient alpha Cronbach ) And yet analysis data reach the two researchers to me What come : " there difference with indication Statistic when Level (0.05) between Average grades students the group Experimental Whose are studying Using the Robin table style, and average grades students the group the officer Whose are studying the way Ordinary ".